Physiological responses and energy system profiling during the simulation of epée competitions in elite fencers - Yang, W. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: To determine sport-specific characteristics, this study aimed to evaluate physiological responses and energy system contributions during simulated epée competitions in elite fencers. METHODS: Ten elite male fencers participated in this study. They performed simulated epée (direct elimination; DE) matches. Simulated epée matches consisted of three rounds of three min each, with one min rest between each round. During these competitions, physiological parameters such as heart rate (HRpeak and HRmean), oxygen uptake (V *O2peak and V *O2mean), metabolic equivalents (METs in V *O2peak and V *O2mean), and blood lactate concentrations (Peak La* and delta La*; *La*) were determined. Furthermore, energy system contributions (oxidative; WOxi, glycolytic; WGly, and phosphagen; WPCr) using the PCr- La*-O2 method and time-motion parameters were calculated. RESULTS: Values of HRpeak, HRmean, and WOxi (%) were significantly higher in the second and third rounds compared with the first round (p < 0.05, p < 0.0001, p < 0.01, and p < 0.0001, respectively). Values of V *O2peak and METs in V *O2peak were significantly higher in the first round compared with the third round (p < 0.05, respectively). Values of *La*, and WGly (kJ and %) were significantly lower in the second and third rounds compared with the first round (p < 0.01, respectively). V *O2mean and METs in V *O2mean were significantly higher in the second round compared with the third round (p < 0.05, respectively). Furthermore, WOxi (kJ and %) was significantly higher in all bouts compared with WPCR and WGly (p < 0.0001, respectively). Low positive and negative correlations were seen between WOxi, V *O2mean, and sum of attacks and defence times (ADT) and the sum of time without attacks and defences (STWAD) (WOxi vs ADT: r = 0.48; R2 = 0.23, V *O2mean vs ADT: r = 0.45; R2 = 0.20, WOxi vs STWAD: r = *0.49; R2 = 0.24, and V *O2mean vs STWAD: r = *0.45; R2 = 0.20, respectively). CONCLUSION: Direct elimination epée matches include high-intensity intermittent exercise and the oxidative energy contribution is 80 to 90% of the total energy demand. Improving aerobic performance such as the increased ability of energy recovery may support high-intensity intermittent actions during entire epée matches (3 rounds) in elite fencers.